Terapi Musik untuk Meningkatkan Kesehatan Mental:: Tinjauan Literatur dalam Perspektif Psikodinamika - Sinaga, Fajry Sub'haan Syah; Winangsit, Emah (Assertive: Islamic Counseling Journal, 2023)
This study discusses the role of music in maintaining mental health through the concepts psychodynamic with id, ego, and super-ego in Sigmund Freud's psychoanalytic theory. The method used is a literature review by searching relevant articles and journals from online databases. The analysis results indicate that music therapy can help individuals express difficult emotions, such as pain, sadness, or anger. In Freud's theory, healthy self-expression and emotional expression are essential for good mental health. Music therapy promises to improve mental health by providing an integrated experience with the emotions that occur when music is played. Previous studies also showed results in line with these findings, but further research is still needed to understand more deeply how music therapy can help improve mental health and how music therapy can be integrated with other therapeutic approaches. These findings indicate novelty in applying Sigmund Freud's psychoanalytic theory in the use of music therapy as a tool for improving mental health.